Prophylactic Potential of Essential Cream Produced from Chromolaena odorata Leaf Extract against Cladophialophora bantiana Strain D12E - Iheukwumere, I. H.; Opara , G. R.; Iheukwumere, M. C.; Okafor, C. F.; Nwakoby, N. E. (IPS Journal of Applied Microbiology and Biotechnology, 2022)
The report of pathogenic potentials of Cladophialophora biatiana in humans, majorly among the farmers is now posing threat to the populace, and the need to search for a preventive measure from readily available, cost-effective, eco-friendly, and natural sources will be an ultimate success to be attained. This study was carried out to evaluate the prophylactic potential of essential cream produced from Chromolaena odorata leaves extract against Cladophialophora biatiana dermatological infection. Soil samples were randomly collected from different farmlands and screened for the presence of Cladophialophora biatiana using appropriate microbiological techniques. The pathological profile of the organism and prophylactic potential of essential cream were assessed by topically exposing them to albino Wistar rats for a period of one month. The study revealed the pathological features of the test isolates; alopecia, discoloration. Scaly, swelling, erythema, patches, macule and erosion were significantly (P < 0.05) reduced to 0.1% / 0% among those rats initially exposed to the studied essential cream. This study has shown that the studied essential cream protected the rats from Cladophialophora biatiana infection and could be used as an alternative prophylactic measure to dermatological infection caused by the studied organism.